Molecular epidemiology of hepatitis D virus circulating in Southwestern Nigeria (2016)
Hepatitis B virus (HBV) and hepatitis D virus (HDV) infections are major public health problems in sub-Saharan Africa. Whereas it is known that HBV infection is endemic in Nigeria, there is only little data about HDV prevalence available. Here, we assessed the HDV seroprevalence and determined the HDV and HBV genotypes distribution among HBsAg positive individuals in Southwestern Nigeria. This cross-sectional study involved 188 serum samples from HBsAg positive outpatients recruited at four tertiary hospitals in Southwestern Nigeria. Anti-HDV antibodies were detected by ELISA while HDV-RNA was detected by RT-PCR. Sequencing followed by phylogenetic analyses and HBV genotype-specific PCR were used to characterize HDV and HBV genotypes, respectively. Out of 188 HBsAg positive serum samples, 17 (9 %) showed detectable HDV-RNA. Anti-HDV antibodies test was possible from 103 samples and were observed in 4.9 % (5/103) patients. There was no significant difference in HDV prevalence between four main cities across the country. 64.7 % of HDV-RNA positive samples were from males and 35.3 % from females (P < 0.05). No significant associations were observed with regard to HDV seroprevalence and available demographic factors. Phylogenetic analyses demonstrated a predominance of HDV genotype 1 and HBV genotype E among the HDV-RNA/HBsAg positive patients. In conclusion, our study showed a high prevalence of HDV infection in HBsAg carriers and the predominance of HDV genotype 1 infection in Nigerian HBV endemic region. The findings contribute to a better understanding of the relevance of HDV/HBV co-infection and circulating genotypes.